Analisis Transportasi Udara, Kunjungan Wisatawan, Nilai Tukar dan Kesempatan Kerja di Indonesia: Pendekatan VECM - Miya Pertiwi; Alpon Satrianto (Universitas Negeri Padang, 2020)
This study aims to identify and analyze responses between air transportation, tourist visits, exchange rates and employment opportunities in Indonesia. This type of research is descriptive and associative, where the data used are secondary data in the form of time series from 2000 fourth quarter to 2018 fourth quarter. This study uses the Vector Error Correction Model (VECM) method through the analysis of block causality test, Impulse Response Function (IRF) and Forecast Error Variance Decomposition (FEVD) to seeing the variability response of an endogenous variable due to the presence of other endogenous variables. The results of this study indicate that: (1) Variability of air transportation is not contributed by the shock of tourist visits, exchange rates and employment opportunities in the short term, but in the long run, variability of air transportation is contributed by shock of tourist visits, exchange rates and employment opportunities. (2) Variability of tourist visits is only influenced by short-term air transportation shock. Whereas air transportation, exchange rates and employment opportunities in the long run contribute to influencing the variability of tourist visits in Indonesia. (3) Exchange rate variability is contributed by air transportation shock, tourist visits and work opportunities in the short and long term. (4) Variability of employment opportunities is contributed by air transportation shock, tourist visits and exchange rates in the short and long term in Indonesia.